2020
DOI: 10.1111/pce.13907
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidases and the evolution of plant salinity tolerance

Abstract: Soil salinization is a major threat to global food security and the biodiversity of natural ecosystems. To adapt to salt stress, plants rely on ROS-mediated signalling networks that operate upstream of a broad array of physiological and genetic processes. A key player in ROS signalling is NADPH oxidase, a plasma-membrane-bound enzyme encoded by RBOH genes. In this study, we have conducted a comprehensive bioinformatic analysis of over 50 halophytic and glycophytic species to link the difference in the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 126 publications
0
27
0
Order By: Relevance
“…These ROS related enzyme activity changes are determined under similar concentration and time point of salt stress. Additionally, it was shown that NADPH oxidases are important in plant response during salinity stress [ 135 ]. Apart from enzymatic antioxidants, there is also an increase in non-enzymatic antioxidants such as AsA (Ascorbate), GSH (glutathione) and tocopherols as observed in Arabidopsis , wheat, sunflower; ryegrass, salicornia [ 87 , 89 , 107 , 121 , 132 , 136 , 137 , 138 , 139 ].…”
Section: Detection Of Salinity Stressmentioning
confidence: 99%
“…These ROS related enzyme activity changes are determined under similar concentration and time point of salt stress. Additionally, it was shown that NADPH oxidases are important in plant response during salinity stress [ 135 ]. Apart from enzymatic antioxidants, there is also an increase in non-enzymatic antioxidants such as AsA (Ascorbate), GSH (glutathione) and tocopherols as observed in Arabidopsis , wheat, sunflower; ryegrass, salicornia [ 87 , 89 , 107 , 121 , 132 , 136 , 137 , 138 , 139 ].…”
Section: Detection Of Salinity Stressmentioning
confidence: 99%
“…Oxidative stress has long been equated with indiscriminate cellular damage, steering decade-long research efforts to prevent ROS accumulation by overexpressing the antioxidant system in various model plants and crops (Kerchev et al, 2015). In multiple cases, and as described below in more detail, such attempts were successful and these transgenic plants displayed enhanced stress dedicated oxidases and peroxidases actively contribute to ROS production (Liu et al, 2020). In photosynthetic tissues, chloroplasts are the major ROS source, with 1 O 2 produced because of the interaction of oxygen with the excited chlorophyll triplet state under light stress (Dmitrieva et al, 2020;Krieger-Liszkay et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ROS also play a role in signal transduction mechanism in the response to stress [ 37 ]. H 2 O 2 as a kind of ROS produced by RBOHF could regulate guard cell signaling and stomatal closure [ 38 , 39 ]. In ROC22, we found that SsRBOHF gene was up-regulated by drought stress and the H 2 O 2 content increased significantly after 4 h of stress, suggesting that the signal transduction mechanism could also occurred in drought tolerant in sugarcane.…”
Section: Discussionmentioning
confidence: 99%